2017
DOI: 10.3389/fpsyg.2017.00716
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Girls’ STEM Identity Formation and Media Images of STEM Professionals: Considering the Influence of Contextual Cues

Abstract: Popular media have played a crucial role in the construction, representation, reproduction, and transmission of stereotypes of science, technology, engineering, and mathematics (STEM) professionals, yet little is known about how these stereotypes influence STEM identity formation. Media images of STEM professionals may be important sources of information about STEM and may be particularly salient and relevant for girls during adolescence as they actively consider future personal and professional identities. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
108
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 105 publications
(175 reference statements)
6
108
0
2
Order By: Relevance
“…For example, the women interviewed by Carlone and Johnson (2007) saw science as a useful tool for pursuing their desire to help others. This more stereotypically feminine goal may contradict the more masculine norms that pervade many scientific disciplines and which is commonly depicted in the media (Steinke, 2017). Future work should examine the overlap that identity has with the domains of competence, performance, and recognition that were proposed by Carlone and Johnson (2007) and Herrera et al (2012).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, the women interviewed by Carlone and Johnson (2007) saw science as a useful tool for pursuing their desire to help others. This more stereotypically feminine goal may contradict the more masculine norms that pervade many scientific disciplines and which is commonly depicted in the media (Steinke, 2017). Future work should examine the overlap that identity has with the domains of competence, performance, and recognition that were proposed by Carlone and Johnson (2007) and Herrera et al (2012).…”
Section: Discussionmentioning
confidence: 94%
“…This corresponds with a sharp decline in students' intentions to major in STEM fields following high school (Berryman, 1983). Depictions of scientists in the media can strongly influence identity development by producing an image of what a STEM professional should be (Steinke, 2017). We propose that, by virtue of being a single-item pictorial measure, the STEM-PIO-1 can be used repeatedly to assess the changes in identification with STEM that can occur as a student progresses through his or her educational track.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that women and men form gender roles in childhood, largely based on their exposure to media and popular culture (Olsson and Martiny 2018;Steinke, 2017). Media images often depict men and women in traditional gender roles, which can negatively impact the STEM career choices women make (Olsson and Martiny 2018;Bian, Leslie, & Cimpian, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A theoretical framework for studying outreach ambassadorship. Recently, researchers have focused on understanding the development of science and engineering identities, or perceptions of one's self as a scientist or engineer, as factors that influence STEM persistence and attrition among historically underrepresented groups of students (Hazari et al, 2013;Papafilippou and Bentley, 2017;Steinke, 2017). Through identity-based perspectives on students' motivation, such as possible selves (Marcus and Nurius, 1986), researchers have established that one's sense of who one is and who one can (or cannot) become within a given field of study, career path, or life course, can act as a substantive source of motivated action (Allie et al, 2009;Oyserman et al, 2004;Nino, 2013;Nystrom, 2009).…”
Section: Introductionmentioning
confidence: 99%